Investigating the Digital Transformation Level Across Industrial Dimensions - Zahra, Masooma; Naqvi, Syed Asif Ali; Anwar, Sofia; Nadeem, Abdul Majeed; Hussain, Bilal (iRASD Journal of Economics, 2024)
Digital transformation drives operational efficiency, customer interaction and innovation. Hence it is necessary for industries to adopt digitalization in order to remain in competition with the global world. Hence, the present study investigated the factors influencing digital transformation within the textile industry, focusing on the roles of industry type, size, and sustainability concerns within industry. Using multinomial logistic regression, the study analyzed data from a sample of 124 textile companies of Pakistan to assess the impact of these factors on different levels of digital transformation. The industry size consists of small, medium and large industries while type of enterprises comprises of spinning, weaving, dying and printing. The digital transformation is classified into four levels in the present study, referring to as traditional, limited, moderate and high. Our results demonstrated that industry type, size, and sustainability concerns significantly impact digital transformation within the textile sector and it was observed that moderate level of digital transformation was found in many industries followed by limited and traditional level where as high level of transformation was found to be lacking, which indicates a strong need for policy making and initiatives in this regard. This research contributes to our understanding of digital transformation dynamics in the textile sector and offers directions for future research in broader contexts.